Pengelolaan Satuan Sekolah Umum dan Madrasah dalam Peningkatan Kualitas Pendidikan - Imam Subekti; Lias Hasibuan; Kasful Anwar; Asniyati Asniyati (Al-Fikr: Jurnal Pendidikan Islam, 2021)
This article aims to explore the normative and philosophical rules regarding the management of primary and secondary school units. This departs from the existence of schools that still need important attention, both public schools under the Ministry of Education and madrasas under the Ministry of Religion. Writing with descriptive analysis method reveals that the rules that discuss this management are contained in the Peraturan Menteri Pendidikan Nasional (Permendiknas) Nomor 19 Tahun 2007 tentang Standar Pengelolaan Pendidikan oleh Satuan Pendidikan Dasar dan Menengah (Education Management Standards by Primary and Secondary Education Units). The regulation contains several important points that must become the standards of educational institutions, both public schools and madrasas, namely the existence of good and measurable program planning, effective and efficient work plans, periodic monitoring and evaluation, qualified and credible leadership, system good information in school. But these standards are minimum standards that must be met by every manager of an education unit. Philosophically, the provisions on management in the regulation have also been historically related to the philosophy of modern education management. However, education that has not been evenly distributed is also a challenge in fully implementing the regulation.